The taller the better? Agglomeration determinants and urban structure - Federico Curci (European Regional Science Association (ERSA), 2015)
The objective of this paper is to establish how urban structure, and in particular height of buildings, can act as a mechanism for agglomeration of firms' establishments. The causes of higher productivity in denser areas have received important attention in the urban economics literature. Input sharing, labour pooling and knowledge spillover are considered as the classical determinants of agglomeration economies. In addition to these forces, firms may be attracted to particular locations because of the prestige associated to particular areas. In order to assess how urban structure and building height can play an important role for agglomeration and the consequent productivity advantages this paper explores the role of skyscraper in influencing the concentration of establishments and employment in U.S. cities. The empirical analysis is conducted using a rich database including all 6 digits NAICS sector, for 14114 ZIP codes for 147 Metropolitan Areas in U.S. from 2000 to 2012. This database has been personally built combining information on geographic establishments location from the U.S. Census Bureau with data on skyscrapers construction from the CTBUH Global Tall Building Database. An important threat to identification comes from reverse causality, and this can arise if the increase in agglomeration in one city leads to demand pressure for more tall buildings. The estimation of the effect of the completion of new tall buildings have been conducted using instrumental variable fixed effects techniques. The dependent variables used are the log number of establishments for each sector in a ZIP area and the log productivity measure. In order to obtain exogeneous variation, the completion of new skyscrapers have been instrumented using the interaction between the distance to bedrocks in one ZIP area with the North-American steel price. One of the most important results is that the effect of newly completed skyscraper on agglomeration differs between sectors. Sectors which are characterized by higher use of human capital and high labour skills are associated with a positive and significant coefficient of new buildings completion on firms agglomeration, such as for the Finance and Insurance sector. The attraction of establishments to the ZIP codes where tall buildings will be completed has an important anticipatory component. At a ZIP level the completion of a new skyscraper is associated with a positive increase in productivity of 20 percent.
Keywords: R30; L70; 330; Agglomeration economies; tall buildings